First Rib Resection Using Videothoracoscopy in Patients With Vascular Thoracic Outlet Syndrome - Agustín Buero; Soledad Olivera Lopez; Gustavo A. Lyons; Leonardo G. Pankl; Pablo Young; Domingo J. Chimondeguy (EJVES Vascular Forum)
Objective: Thoracic outlet syndrome (TOS) comprises a series of signs and symptoms produced by compression of neurovascular structures in any of the anatomical spaces of the thoracic outlet. First rib resection is a therapeutic alternative to decompress the structures of the thoracic outlet at the costoclavicular space. Traditional surgical approaches include transaxillary, supraclavicular, and infraclavicular access. The objective was to describe the surgical experience and follow up results of first rib resection using video assisted thoracoscopic surgery (VATS) in patients with vascular TOS. Methods: Observational descriptive study based on a retrospective single centre analysis of a prospective database. Patients diagnosed with vascular TOS who underwent VATS first rib resection from January 2017 to December 2023 were included. The diagnosis for each subtype was based on the criteria defined in the standards of the American Society for Vascular Surgery in TOS. Among other things, the response to initial anticoagulation, peri-operative data, complications, symptom improvement, duration of post-operative anticoagulation, and symptom recurrence were investigated. Results: Twenty nine patients diagnosed with vascular TOS who underwent VATS first rib resection, three of whom had bilateral procedures, were included. The total number of costal rib resections performed was 32 (31 venous TOS and one arterial TOS). The mean age was 29.1 ± 10.4 years and mean hospital stay was 2.7 ± 1.2 days. There were neither conversions to open surgery nor intra-operative complications, but there were two major post-operative complications (6.25%). No recurrences were detected during midterm follow up (median of 17.9 months, interquartile range 7.3, 45). Conclusion: VATS first rib resection is a safe and feasible procedure. Unlike traditional approaches, this procedure allows physicians to make the resection under complete vision of the anatomical structures of the thoracic outlet reducing intra-operative complications and, if necessary, entire rib resection can be performed.